The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1103/physrevd.78.044022
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous breaking of conformal invariance, solitons, and gravitational waves in theories of conformally invariant gravitation

Abstract: We study conformal gravity as an alternative theory of gravitation. For conformal gravity to be phenomenologically viable requires that the conformal symmetry is not manifest at the energy scales of the other known physical forces. Hence we are required to find a mechanism for the spontaneous breaking of conformal invariance. In this paper we study the possibility that conformal invariance is spontaneously broken due to interactions with conformally coupled matter fields. The vacuum of the theory admits confor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…We have shown that transverse, traceless, plane fronted monochromatic gravitational waves given by the ansatz (4) are actually conformally and coordinate equivalent to flat Minkowski space-time. This generalizes to all orders, the result found to second order in [11] that transverse, traceless, linearized plane waves carry no energy to second order in Weyl gravity and that found in [1]. However our general result here follows from the unexpected discovery that such deviations from Minkowski space-time are actually trivial, they are just conformal and coordinate artifacts.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We have shown that transverse, traceless, plane fronted monochromatic gravitational waves given by the ansatz (4) are actually conformally and coordinate equivalent to flat Minkowski space-time. This generalizes to all orders, the result found to second order in [11] that transverse, traceless, linearized plane waves carry no energy to second order in Weyl gravity and that found in [1]. However our general result here follows from the unexpected discovery that such deviations from Minkowski space-time are actually trivial, they are just conformal and coordinate artifacts.…”
Section: Discussionsupporting
confidence: 60%
“…Since our solution is valid for any strength of the fluctuation, the Weyl gravitational field equations must be valid order by order in the parameter corresponding to the strength of the fluctuation. The result in [11] was an explicit verification of this fact for the second order terms.…”
Section: Discussionmentioning
confidence: 59%
“…[29] (see also Refs. [30,31]) considered spontaneous symmetry breaking in Weyl gravity and showed that this can provide a mechanism to generate a scale in the theory. Taking advantage of the independence of the Lagrangian on the t− and φ−coordinates, and using θ = π/2 as the plane of the circular orbits without loss of generality due to spherical symmetry, the Euler-Lagrange equations of motion are given by…”
Section: Circular Orbits and Kepler's Third Lawmentioning
confidence: 99%
“…As a conclusion, if a highly probable linear quantum of gravitational field exist, it could not be represented by Weyl gravity, since linear Weyl gravitational field does not transform under UIR of the conformal and de Sitter groups. Other authors have concluded the same through different methods [5,10].…”
Section: Introductionmentioning
confidence: 80%